FAKTOR RESIKO YANG BERHUBUNGAN DENGAN LESI PRAKANKER SERVIKS PADA WPS TIDAK LANGSUNG DI WILAYAH KERJA PUSKESMAS MENINTING - Irmayani Irmayani (Jurnal Kesehatan Prima, 2014)
Abstract: Cervical cancer is the second cause of death for women in Indonesia. Indirect FSWs at risk for cervical cancer because social lifestyle that increase the likelihood of high-risk HPV infection. Meninting health center located in a major tourist destination and actively conduct outreach, mentoring and already implementing early detection of cervical cancer by IVA since April 2013. The purpose of the study to analyze the risk factors associated with precancerous lesions in Indirect FSWs the Puskesmas Meninting in 2013. PHC Meninting using observational methods to the total population of 148 people Indirect FSWs recorded unmarried coming to IVA examination at the Meninting health center in 2013 results showed that the variables associated with cervical precancerous lesions is age (p = 0.001) and smoking behavior (p = 0.013) and the most dominant variable causes the occurrence of precancerous lesions of the cervix is the smoking behavior with OR 8.022. For health workers and related institutions should be to provide health promotion, especially the emphasis on the effects of smoking and unsafe sexual behavior.